2004
DOI: 10.1081/ese-120037874
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mixture Ratio and Hydraulic Retention Time on Single-Stage Anaerobic Co-digestion of Food Waste and Waste Activated Sludge

Abstract: The biochemical methane potential (BMP) test was used to evaluate the anaerobic biodegradabilities of food waste (FW), waste activated sludge (WAS), and the mixtures having the ratios of 10:90, 30:70, 50:50, 70:30, and 90:10 (FW:WAS) on a volatile solid (VS) basis. The carbon/nitrogen (C/N) ratio and the biodegradability of the mixtures improved from 6.16 to 14.14 and increased from 36.6 to 82.6% as the FW proportion of the mixture increased from 10 to 90%, respectively. The stability and performance of the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(65 citation statements)
references
References 20 publications
7
57
1
Order By: Relevance
“…The experimental results indicate that USS digestion improved the biogas yield up to 20%, 57% and 62% of 70/30 (WUS-OFMSW), 50/50 (WAS-OFMSW) and 100% of USS respect to the same ratio of WAS-OFMSW and 100% of WAS, CH 4 yield was increased up to 94% by (50/50) WUS-OFMSW. Moreover, our results which were obtained for WAS and its mixtures with OFMSW accord with results reported in Reference [9,11] in the terms of behavior and biogas/methane yield, and CH 4 yields were superior to those obtained in Reference [15,[37][38][39]. The co-digestion between WUS and OFMSW is a suitable solution for waste management and an alternative renewable energy source from the conversion of wastes into biogas, these observation accords with [40].…”
Section: Resultssupporting
confidence: 79%
“…The experimental results indicate that USS digestion improved the biogas yield up to 20%, 57% and 62% of 70/30 (WUS-OFMSW), 50/50 (WAS-OFMSW) and 100% of USS respect to the same ratio of WAS-OFMSW and 100% of WAS, CH 4 yield was increased up to 94% by (50/50) WUS-OFMSW. Moreover, our results which were obtained for WAS and its mixtures with OFMSW accord with results reported in Reference [9,11] in the terms of behavior and biogas/methane yield, and CH 4 yields were superior to those obtained in Reference [15,[37][38][39]. The co-digestion between WUS and OFMSW is a suitable solution for waste management and an alternative renewable energy source from the conversion of wastes into biogas, these observation accords with [40].…”
Section: Resultssupporting
confidence: 79%
“…Budzianowski [66] has reported that the concentration of CH 4 in biogas can reach 98-99% by the injection of coke oven gas to an AD reactor (COG-AD). Furthermore, Heo et al [67] have experimentally demonstrated in Korea that the degradability of vegetables varied from 65-70% with a methane yield of 0.49 L g -1 vs at 35ºC after 40 days HRT, whereas Zhang et al [68] have equally noted that food waste contained appropriate nutrients for anaerobic microorganisms and through batch digestion under thermophilic conditions (50ºC) after 28 days, biogas was produced at a magnitude 0.44 L g -1 vs.…”
Section: Second Scenariomentioning
confidence: 99%
“…In addition, the nutrient content of OFMSW can be recovered by application of the residues from the anaerobic digestion processes for soil conditioning and fertilization. Several studies report on the use of OFMSW for co-digestion with sewage sludge (e.g., Hartmann et al 2002;Sosnowski et al 2003;Heo et al 2004;Bolzonella et al 2006;Kaan Dereli et al 2010). In an investigation of the co-digestion of waste-activated sludge with OFMSW, Bolzonella et al (2006) observed a 24% increase in biogas yield (from 0.21 to 0.26 m 3 kgVS −1 ), with an increase in the OLR from 1.0 to 1.2 kgVS m −3 day −1 .…”
Section: Introductionmentioning
confidence: 99%
“…During stepwise increase of the OLR, there was no indication of disturbances of the digester performance (Aichinger et al 2015). Heo et al (2004) investigated the stability and efficiency of a laboratoryscale anaerobic reactor co-digesting food waste (FW) and waste-activated sludge (WAS) at various hydraulic retention times (HRT: 10-20 days) and waste mixture ratios (FW:WAS). They reported an HRT of 13 days and a FW: WAS ratio of 50:50 on VS basis as optimum, which yielded a specific methane production of 0.32 m 3 kgVS −1 and a VS reduction of 57% at an OLR of 2.4 kgVS m −3 day −1 .…”
Section: Introductionmentioning
confidence: 99%